(untitled) (IUBAT Review, 2026)
This paper reviews current research on the relationship between motivation and success in English language learning, emphasizing the critical role of intrinsic and extrinsic motivation. Theoretical frameworks such as Gardner’s Socio-Educational Model and Deci and Ryan’s Self-Determination Theory are explored, along with Dörnyei’s L2 Motivational Self System, to understand how motivation influences language learning outcomes. The paper highlights the importance of individual differences, social contexts, and educational environments in shaping motivation. It also discusses the implications for teachers in creating a supportive and engaging learning atmosphere and using technology to enhance motivation. Future research directions are suggested, focusing on the dynamic interplay of motivational factors, technological integration, and cultural contexts to provide a more comprehensive understanding of motivation in language learning. By addressing these aspects, the paper aims to inform and improve educational practices, ultimately supporting successful language learning experiences. IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 329-364